THE INFLUENCE OF CELEBRITY ENDORSER AND PRODUCT QUALITY ON PURCHASE DECISIONS THROUGH BRAND IMAGE AS INTERVENING VARIABLES IN "WARDAH" COSMETICS - Muslih Muslih; Muhammad Irfan Nasution; Kiky Mentari (Proceeding International Seminar of Islamic Studies, 2021)
The purpose of this study was to analyze the direct and indirect effects of Celebrity Endorser, Product Quality, and Brand Image as intervening variables on Purchasing Decisions. The population of this research is wardah cosmetic users at the Faculty of Economics and Business UMSU. The number of samples is 100 respondents with asidental sampling. Data obtained by questionnaire. Research variables Celebrity Endorser (X1), Product Quality (X2), Brand Image (Z) and Purchase Decision (Y). Data analysis with percentage percentage descriptive, Path Analysis, Classical Assumption Test and Hypothesis Test. The results of this study indicate that the variable Celebrity Endorser (X1) has a direct effect on Purchasing Decisions (Y). And there is no direct effect of Product Quality (X2) on Purchasing Decisions. Brand Image Variable (Z) has a direct effect on Purchasing Decisions (Y). Variable Celebrity Endorser (X1) and Product Quality (X2) have a direct effect on Purchasing Decisions (Y). Path analysis results show that Celebrity Endoser (X1) has no indirect effect through Brand Image (Z) on Purchasing Decisions (Y), and there is an indirect influence on Product Quality (X2) through Brand Image (Z) on Purchasing Decisions ( Y), so it can be said that brand image mediates the influence of product quality on purchasing decisions. The conclusion from this research is that Celebrity Endorser, product quality, and brand image as intervening variables have direct and indirect effects on purchasing decisions. It is suggested that wardah should increase the use of Celebrity Endorse, such as the use of celebrities which are currently popular In terms of product quality, Wardah should be able to increase the reliability of Wardah products such as the safety of Wardah cosmetics.Keywords: Celebrity Endorser, Product Quality, Brand Image, Purchase Decision